Modelo de avaliação do desempenho ambiental de inovações tecnológicas agroindustriais, considerando conceito de ciclo de vida e a vulnerabilidade ambiental: AMBITEC - ciclo de vida - Figueirêdo, Maria Cléa Brito de (2008)
Agro-industrial technological innovations have met the growing food demand and sprung economic development in Brazil and in other parts of the world. However, the perception that economic development depends on environmental conservation and on an educated, healthy and participative society to be sustainable in the long run calls for the use of environmental evaluation tools in the innovation process. This work aims to contribute to the sustainable development of agro-industrial innovations, presenting the Ambitec-Life Cycle, a model that evaluates the environmental performance of agro-industrial innovations, considering the life cycle concept and the vulnerability of the watersheds where each phase of a technology life cycle occurs. The proposed model took as initial reference the Ambitec-Agro System, currently adopted by the Brazilian Agriculture Research Corporation (EMBRAPA), in the evaluation of its innovations. The Ambitec-Agro evaluates the performance of an innovation in comparison with an existing technology, focusing the analysis on the innovation-adopting establishment scale. The multicriteria analysis and the set of rules ISO 14.040, related to life cycle analysis, were used to expand the scope of the Ambitec-Agro System, introducing in the performance evaluation other phases of an innovation life cycle: raw material production or waste disposal (in case the technology causes waste disposal instead of its use as raw material), technology production, technology use and its final disposal. In each life cycle phase of an innovation, the environmental vulnerability of the watersheds where the production units are located is also evaluated. The environmental vulnerability refers to the issues currently related to agro-industrial activities that can cause impact at the watershed level, which are: loss of biodiversity, soil erosion, soil compaction, soil salinization and sodification, desertification, water scarcity and water pollution. The vulnerability analysis generates an index to each watershed that enters at a technology performance evaluation as a weight to those performance indicators that represent sources of pressure and potential impact at the watershed scale. The Ambitec-Life Cycle was implemented in Excel spreadsheets in order to facilitate data input and results generation in tables and graphics formats. The sensitivity analysis of the model shows that change in the value of each indicator contributes to change in the final environmental performance index. However, a change in the indicator value can lead to higher change in the final performance index when this change inverts the position of an innovation in relation to the compared technology, turning an innovation indicator value higher or smaller than the comparing technology indicator value. The model was applied in the evaluation of the innovation “immature coconut substrate (ICS)”, developed by Embrapa Tropical Agroindustry, as compared to the existing substitute technology “mature coconut substrate (MCS)” in rose production of the Carola variety. Considering indicators’ average values, the ICS environmental performance was higher than the MCS performance in the phases of raw material disposal and use of substrate in rose seedling production and lower in the phases of substrate production, substrate use in rose production and substrate final disposal, revealing that changes in the production process must be developed and implemented in order to improve ICS final results. This environmental evaluation reinforced the importance of taking into account all the phases of a technology life cycle to compare its performance against its potential substitutes, in order to identify opportunities for improvements that benefits its entire life cycle.